KOKAND IS THE LAND OF SCIENTISTS - Islamov Abdulaziz Latif son; Ozodkhodjaeva Lobarkhon Akramjon girl (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, Kokand is not only a city of poets, scientists and artists, but also a worldrenowned world of scientists.